Maturation of auditory brainstem projections and calyces in the congenitally deaf (dn/dn) mouse - Youssoufian, Monique; Couchman, Kiri; Shivdasani, Mohit; Paolini, Antonio G.; Walmsley, Bruce (John Wiley and Sons, 2007)
he deaf dn/dn mouse is a valuable model of human congenital deafness. In this study we used the lipophylic dye DiA to trace auditory nerve and cochlear nucleus projections in the dn/dn mouse. In both normal and deaf mice, the ipsilateral projections from the anteroventral cochlear nucleus (AVCN) to the lateral superior olive (LSO), and the contralateral projections from the AVCN to the medial nucleus of the trapezoid body (MNTB) were intact. With age, there was a noted increase in the fenestration of the endbulb and calyx of Held, and this morphological maturation was also observed in the deaf mice, although there was a significant difference in total endbulb volume at P20 between normal and deaf mice. However, total calyceal volume was not significantly different between normal and deaf mice. There was electrophysiological evidence of in vivo spontaneous ventral cochlear nucleus activity in normal and deaf animals, indicating that this activity may be responsible for the appropriate connectivity in the deaf mice. Our results indicate that congenital deafness caused by the dn/dn mutation does not result in aberrant projections between the AVCN and the ipsilateral MNTB and contralateral LSO but can cause abnormalities in endbulb size.
Keywords: deafness; calyx of Held; endbulb of Held; cochlear nucleus; superior olivary complex